Murine and Human Cathelicidins Contribute Differently to Hallmarks of Mastitis Induced by Pathogenic Prototheca bovis Algae - Shahid, Muhammad; Cavalcante, Paloma Araujo; Knight, Cameron G.; Barkema, Herman W.; Han, Bo; Gao, Jian; Cobo, Eduardo R. (Frontiers in Cellular and Infection Microbiology, 2020)
Prototheca bovis (formerly P. zopfii genotype-II) is an opportunistic, achlorophyllous alga that causes mastitis in cows and skin disease in cats and dogs, as well as cutaneous lesions in both immunocompetent and immunosuppressed humans. Antifungal medications are commonly ineffective. This study aimed to investigate innate immune responses contributed by cathelicidins to P. bovis in the mammary gland using a mastitis model in mice deficient in the sole murine cathelicidin (Camp). We determined P. bovis caused acute mastitis in mice and induced Camp gene transcription. Whereas Camp-/- and Camp+/+ littermates had similar local algae burden, Camp+/+ mice produced more pro-inflammatory cytokines, TNF α and Cxcl-1. Likewise, Camp+/+ bone marrow-derived macrophages were more responsive to P. bovis, producing more TNF α and Cxcl-1. Human cathelicidin (LL-37) exhibited a different effect against P. bovis; it had direct algicidal activity against P. bovis and lowered TNF α, Cxcl-1, and IL-1β production in both cultured murine macrophages and mammary epithelial cells exposed to the pathogenic algae. In conclusion, cathelicidins were involved in protothecosis pathogenesis, with unique roles among the diverse peptide family. Whereas endogenous cathelicidin (Camp) was key in mammary gland innate defense against P. bovis, human LL-37 had algicidal and immunomodulatory functions.